"Green" synthesis of highly luminescent lead-free Cs2AgxNa1−xBiyIn1−yCl6 perovskites. Issue 27 (14th June 2022) - Stroyuk, Oleksandr; Raievska, Oleksandra; Barabash, Anastasia; Batentschuk, Miroslaw; Osvet, Andres; Fiedler, Saskia; Resch-Genger, Ute; Hauch, Jens; Brabec, Christoph J.
Abstract : Microcrystalline Cs2 Ag x Na1− x Bi y In1− y Cl6 perovskites with tailored composition emitting broadband yellow-white photoluminescence with a quantum yield of up to 92% were produced by a new "green" approach under ambient conditions. Abstract : A new "green" and mild synthesis of highly stable microcrystalline Cs2 Ag x Na1− x Bi y In1− y Cl6 (CANBIC) perovskites under ambient conditions was developed that is scalable to the multi-gram production. Under UV illumination, the CANBIC perovskites emit intense broadband photoluminescence (PL) with a quantum yield (QY) of 92% observed for x = 0.35 and y = 0.01–0.02. The combination of strong UV absorbance and broadband visible emission, high PL QY, and long PL lifetimes of up to 1.4 μs, along with an outstanding stability makes these CANBICs a promising material class for many optical applications.